Heroines and Local Girls : the Transnational Emergence of Women's Writing in the Long Eighteenth Century. - Cheek, Pamela L. (Haney Foundation Ser., 2019)
In Heroines and Local Girls, Pamela L. Cheek explores the rise of women's writing as a distinct, transnational category in Britain and Europe over the long eighteenth century, characterized by stories about heroines who transcend their gendered destiny.